The Roles of Perceived Risks and Price on the Purchase Intention of China-Made Home Appliances Among Career Women in Malaysia - Hashim, Noor Azmi; Husin, Zolkafli; Othman, Ismail Lebai; Md Zain, Ali Yusob (Universiti Utara Malaysia Press, 2017)
The purpose of this research paper is to report on the purchase intention of China-made home appliances among career women in Malaysia. The purchase intention is hypothesised to be influenced by the price and preference of todays career women who are indifferent to the products country of origin and brand. Data were collected by random sampling from 430 career women in selected states in Malaysia in 2016 and were used to test the hypotheses. Survey questionnaires were used to collect the data by utilising a self-administrated method. The relationships between price, perceived risks, attitude toward brand, and purchase intention were tested in this study. The results showed that price is the main factor being considered by the career women in Malaysia when they decide to purchase China-made home appliances. This study implied that marketers need to capitalise on pricing strategy in order to market their home appliances among career women.